2017
DOI: 10.1159/000475881
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy: Readability of ACC/AHA Online Patient Education Material

Abstract: Objectives: To determine whether the online patient education material offered by the American College of Cardiology (ACC) and the American Heart Association (AHA) is written at a higher level than the 6th-7th grade level recommended by the National Institute of Health (NIH). Methods: Online patient education material from each website was subjected to reading grade level (RGL) analysis using the Readability Studio Professional Edition. One-sample t testing was used to compare the mean RGLs obtained from 8 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 11 publications
1
25
0
2
Order By: Relevance
“…Moreover, the NIH suggests using a 6th grade level for medical material written for the public. Kapoor et al [5] revealed these startling facts in his paper in this issue of Cardiology . Furthermore, a 2006 report from the US Department of Health and Human Services found only 12% of adults in the US have proficient health literacy.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…Moreover, the NIH suggests using a 6th grade level for medical material written for the public. Kapoor et al [5] revealed these startling facts in his paper in this issue of Cardiology . Furthermore, a 2006 report from the US Department of Health and Human Services found only 12% of adults in the US have proficient health literacy.…”
mentioning
confidence: 93%
“…Furthermore, a 2006 report from the US Department of Health and Human Services found only 12% of adults in the US have proficient health literacy. More than a third of adults have low health literacy levels, which makes it difficult for them to deal with common health tasks, such as following directions for how to use prescription medications [5]. The problem is exacerbated in the elderly and in those patients whose primary language is not English.…”
mentioning
confidence: 99%
See 3 more Smart Citations